2015
DOI: 10.2196/mental.4294
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Issues in the Development of a Virtual Mental Health Clinic for University Students: A Qualitative Study

Abstract: BackgroundThere is a growing need to develop online services for university students with the capacity to complement existing services and efficiently address student mental health problems. Previous research examining the development and acceptability of online interventions has revealed that issues such as privacy critically impact user willingness to engage with these services.ObjectiveTo explore university student perspectives on privacy issues related to using an online mental health service within the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…For instance, studies in e-mental health research have used focus group interviews [ 6 , 28 , 29 ]. Such qualitative studies in university settings have shown concerns about data security and confidentiality that can turn out as key obstacle to use e-mental health services [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies in e-mental health research have used focus group interviews [ 6 , 28 , 29 ]. Such qualitative studies in university settings have shown concerns about data security and confidentiality that can turn out as key obstacle to use e-mental health services [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Focus group participants were asked a series of questions relating to help-seeking preferences for mental health problems (both offline and on the Internet) and their views toward the development of a virtual mental health clinic for university students. Data relevant to the development of the virtual clinic have been published elsewhere (see [ 10 ] and [ 11 ]). The current paper focuses on participant responses to the following question: “What do you think about using the Internet to get support for mental health or emotional problems?” Participants who sought clarification about the meaning of “using the Internet” were provided with typical examples of Web-based mental health resources (eg, informational websites, self-help therapy programs, and peer-to-peer support networks such as forums and chat platforms).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, most studies targeting the general population in this field directed to low willingness to future use of e-mental health services in case of emotional distress [10,26-29]. Potential reasons for negative expectations and attitudes toward e-mental health include concerns on privacy [28,30,31], communication [9], therapeutic alliance, and unfamiliarity with technology [1]. Facilitators or positive attitudes and perspectives of Internet-based therapies need to be explored.…”
Section: Introductionmentioning
confidence: 99%